Local community's perception of tourism in Redang Island, Malaysia - Kunasekaran, Puvaneswaran; Talib, Ahmad Tarmizi (Korean Academic Society of Culture and Tourism, 2013)
This paper presents a preliminary study of the local community`s perception on eco tourism in Redang Island, Malaysia. The basic understanding of the local community`s view is important before conducting further research because they are the key players of the industry. Apart from that this paper also covers an overall review and conceptualization of eco tourism within the community development perspective. Four variables, job opportunity, economic benefit, quality of life, preventing migration were measured using quantitative tool. Generally, the community is in full support of tourism business in their area and ready to explore more if given appropriate opportunity. It is also feared that the migration of the younger generation to urban areas can be worse and could be only prevented by boosting the job opportunities in Redang Island. The outcome will be significant to understand the host-tourism relationship that will stress the importance of co-management approach to encourage a sustainable tourism practice.